A novel criterion for the prediction of meso-scale defects in textile preforming. (15th October 2019) - Matveev, Mikhail Y.; Endruweit, Andreas; De Focatiis, Davide S.A.; Long, Andrew C.; Warrior, Nicholas A.
Abstract: In numerical simulations of reinforcement preforming, fabrics are often modelled using continuum approaches with homogenised material properties in order to reduce the computational costs. To predict the occurrence of meso-scale defects, in particular when membrane finite elements are used for modelling, a novel wrinkling criterion is proposed here. This criterion relates the onset of reinforcement buckling to material and process parameters. It is demonstrated that the criterion correctly predicts the occurrence of meso-scale defects and is more accurate than criteria based on a constant shear locking angle or critical strain for the defect onset, which do not to take into account local processing conditions such as friction or normal pressure.